Formation of chromium–nickel steel cladding layers on petrochemical equipment components using the double-electrode surfacing method - Elsukov Sergey; Zorin Ilya; Lysak Vladimir; Kharlamov Valentin; Fastov Sergey (EPJ Web of Conferences)
This article discusses the results of investigating the structure of chromium–nickel metal obtained through electric arc surfacing with single and double electrodes in a protective gas. It provides recommendations for forming a defect-free cladding layer by welding with double electrodes. The results show that double electrodes can achieve comparable resistance to intergranular corrosion while reducing electrode metal consumption by approximately 30–35%. Additionally, this method results in a more technologically advanced form of deposited beads.